A mobile application to enhance mobility of people with permanent or temporary mobility disability : a case study in Portugal - Paiva, Sara (2022)
This paper presents a mobile application developed in conjunction with the City Hall from Viana do Castelo, a city in the north of Portugal. This application targets people with permanent or temporary reduced mobility and intends to show them information about taxi points, parking spaces and reference points in the city with the possibility to navigate to them using an optimized algorithm, based on routes defined for each segment (deaf people, visually impaired people, etc.). The Dijkstra?s algorithm was used to implement the shortestPath given an origin, destination and segment. In this paper we present implementation details as well as final layouts of the prototype. At the current moment, the application is ended and will soon enter in usability tests with the users.